2023
DOI: 10.7759/cureus.45416
|View full text |Cite
|
Sign up to set email alerts
|

Tofacitinib in Steroid-Refractory Acute Severe Ulcerative Colitis: A Retrospective Analysis

Sayan Malakar,
Srikanth Kothalkar,
Umair Shamsul Hoda
et al.

Abstract: Introduction: Steroid-refractory acute severe ulcerative colitis (ASUC) patients are at the highest risk of colectomy. Among the available options, cyclosporine and infliximab have similar efficacy but infliximab is a costly drug and cyclosporine has multiple side effects like kidney injury, neurotoxicity, and dyselectrolytemia. Surgical management is often associated with higher morbidity. Newer oral small molecules like Janus kinase inhibitors are the ideal molecules to bridge the gap. Tofacitinib has alread… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…The median follow-up period was extended to six months (IQR: 1-12 months). However, the study reported that one patient required colectomy, and another experienced varicella zoster reactivation, leading to treatment discontinuation [17]. Despite the promising initial response, this investigation underscores the need for further exploration of the long-term efficacy and associated risks of tofacitinib in the context of steroid-refractory ASUC.…”
Section: Tofacitinib In Asucmentioning
confidence: 89%
See 1 more Smart Citation
“…The median follow-up period was extended to six months (IQR: 1-12 months). However, the study reported that one patient required colectomy, and another experienced varicella zoster reactivation, leading to treatment discontinuation [17]. Despite the promising initial response, this investigation underscores the need for further exploration of the long-term efficacy and associated risks of tofacitinib in the context of steroid-refractory ASUC.…”
Section: Tofacitinib In Asucmentioning
confidence: 89%
“…In another retrospective study spanning from January 2021 to July 2023, eight patients diagnosed with ASUC who was unresponsive to intravenous hydrocortisone were analyzed for their responses to tofacitinib [17]. With a mean age of 39 ± 15 years and a predominantly female composition (87.5%), these patients displayed 87.5% positive responses to oral tofacitinib at a dosage of 10 mg twice a day within the initial five days of treatment.…”
Section: Tofacitinib In Asucmentioning
confidence: 99%